Mortality and ionising radiation exposures among workers employed at the Fernald Feed Materials Production Center (1951–1985). Issue 7 (15th January 2013) - Silver, Sharon R; Bertke, Stephen J; Hein, Misty Jena; Daniels, Robert D; Fleming, Donald A; Anderson, Jeri L; Pinney, Susan M; Hornung, Richard W; Tseng, Chih-Yu
Abstract : Objectives: To examine mortality patterns and dose-response relations between ionising radiation and mortality outcomes of a priori interest in 6409 uranium workers employed for at least 30 days (1951–1985), and followed through 2004. Methods: Cohort mortality was evaluated through standardised mortality ratios (SMR). Linear excess relative risk (ERR) regression models examined associations between cause-specific mortality and exposures to internal ionising radiation from uranium deposition, external gamma and x-ray radiation, and radon decay products, while adjusting for non-radiologic covariates. Results: Person-years at risk totalled 236 568 (mean follow-up 37 years), and 43% of the cohort had died. All-cause mortality was below expectation only in salaried workers. Cancer mortality was significantly elevated in hourly males, primarily from excess lung cancer (SMR=1.25, 95% CI 1.09 to 1.42). Cancer mortality in salaried males was near expectation, but lymphohaematopoietic malignancies were significantly elevated (SMR=1.52, 95% CI 1.06 to 2.12). A positive dose-response relation was observed for intestinal cancer, with a significant elevation in the highest internal organ dose category and a significant dose-response with organ dose from internal uranium deposition (ERR=1.5 per 100 μGy, 95% CI 0.12 to 4.1). Conclusions: A healthy worker effect was observed only in salaried workers. Hourly workers had excess cancer mortality compared with the US population, although there was little evidence of a dose-response trend for any cancer evaluated except intestinal cancer. The association between non-malignant respiratory disease and radiation dose observed in previous studies was not apparent, possibly due to improved exposure assessment, different outcome groupings, and extended follow-up.